2018
DOI: 10.1038/s41598-018-24388-x
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinous plankton is important in the diet of European eel (Anguilla anguilla) larvae in the Sargasso Sea

Abstract: Limited insight into eel larvae feeding and diet prevents a holistic overview of the life-cycle of catadromous eels and an understanding of the ecological position of their early stages in marine waters. The present study evaluated the diet of larval European eel, Anguilla anguilla - a critically endangered species. Next-generation 18S rRNA gene sequencing data of Sargasso Sea eel larvae gut contents and marine snow aggregates was compared with a reference plankton database to assess the trophic relations of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 71 publications
4
54
0
Order By: Relevance
“…All the individuals tested showed positive detection of A. coerulea in their gut contents, with relatively high DNA concentrations. The consumption of gelatinous organisms by eels was also previously reported for their larvae (leptocephali) in the Sargasso Sea (Riemann et al 2010;Ayala et al 2018). Although there is a progressive ontogenic change in the diet of the eels (Costa et al 1992;Proman and Reynolds 2000), it is not surprising that they retain the ability to feed on gelatinous organisms.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…All the individuals tested showed positive detection of A. coerulea in their gut contents, with relatively high DNA concentrations. The consumption of gelatinous organisms by eels was also previously reported for their larvae (leptocephali) in the Sargasso Sea (Riemann et al 2010;Ayala et al 2018). Although there is a progressive ontogenic change in the diet of the eels (Costa et al 1992;Proman and Reynolds 2000), it is not surprising that they retain the ability to feed on gelatinous organisms.…”
Section: Discussionsupporting
confidence: 61%
“…Due to these modern techniques, the list of jellyfish predators has been growing and now includes commercially important fishes such as herring (Clupea harengus), whiting (Merlangius merlangus), bluefin tuna (Thunnus thynnus) and swordfish (Xiphias gladius) (Cardona et al 2012;Lamb et al 2017). Jellyfish were also shown to be of high importance in the diet of the larvae of a critically endangered fish, the European eel, Anguilla anguilla (Ayala et al 2018) and to be ingested even by herbivorous fishes (Bos et al 2016). Likewise, cephalopods, anemones, crabs, echinoderms and several species of birds have been reported to feed on jellyfish (Ates 2017;Hoving and Haddock 2017;McInnes et al 2017;Phillips et al 2017;Thiebot et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example in a recent study of two species of albatross across eight breeding sites in which >1000 scat samples were analyzed, scyphozoan jellyfish represented 20% of the food DNA sequences, second only in importance to bony fish (66% of food DNA sequences) and ahead of crustaceans (8% of food DNA sequences) [21]. Similarly, next generation sequencing has been used to determine the gut contents of the leptocephali larvae of the endangered European eel Anguilla anguilla in the Sargasso Sea [27]. With gelatinous zooplankton (mostly siphonophores) representing 76% of the DNA sequences detected, it is clear that leptocephali larvae have an apparent preference for consuming jellyfish.…”
Section: Old Question New Methodologies: Recent Evidence For Jellyfimentioning
confidence: 99%
“…However, for many other marine animals that remain at sea continuously, such as fish, collecting fecal samples is not so straightforward. [15,22,27,31,51,88], turtles [9,16,32], crab [28,89], rock lobster larvae [36] and sea cucumber [5]. (B) Widespread consumption of jellyfish may be facilitated by their rapid digestion which helps to counterbalance their low energy density.…”
Section: Dna Metabarcodingmentioning
confidence: 99%
“…Mesozooplankton (>200 µm) production in the Sargasso Sea is highest during February through April (Steinberg et al 2012), coincident with the American Eel spawning season. Ayala et al (2018) found that European Eel leptocephali often consume gelatinous hydrozoa plankton materials.…”
Section: Discussionmentioning
confidence: 99%